THE EFFECT OF USING THE HARRISON & BRAMSON MODEL ON STUDENTS' ACHIEVEMENT IN KURDISH LANGUAGE AND LITERATURE IN PRAGMATICS. - Othman, Ayad; Nabi, Molod; عه‌لی , شێرزاد (Humanities Journal of University of Zakho, 2024)
The aim of the research is to identify the effectiveness of the Harrison & Bramson model in improving the achievement of fourth-grade students in the Kurdish Language and Literature department in a pragmatics subject. The researchers adopted the experimental design of equal groups with a post-test. The research sample included fourth grade students/ Department of Kurdish Language and Literature at the College of Basic Education at the University of Duhok for the academic year (2021-2022), totaling (75) male and female students, divided into two groups (A) and (B) randomly. The (38) students of the experimental group (B) were taught according to the Harrison and Bramson model, and the students of the control group (A), numbering (37) students, were taught according to the usual method used. The researchers prepared an achievement test that included (40) items and determined its psychometric characteristics. After the completion of the experiment, which lasted a full semester, the researchers applied the tool, extracted the data, and conducted the analysis using the (t-test) with it. The results showed that the Harrison and Bramson model had a significant impact on the achievement among the students of the experimental group compared to their peers in the control group.